2021
DOI: 10.1101/2021.02.28.433243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tetraploidy accelerates adaption under drug-selection in a fungal pathogen

Abstract: Baseline ploidy significantly impacts evolutionary trajectories, and in particular, tetraploidy has been associated with higher rates of adaptation compared to haploidy and diploidy. While the majority of experimental evolution studies investigating ploidy use Saccharomyces cerivisiae, the fungal pathogen Candida albicans is a powerful system to investigate ploidy dynamics, particularly in the context of antifungal drug resistance. C. albicans laboratory and clinical strains are predominantly diploid, but have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…A second evolution experiment done at the same subinhibitory level of FLC, however, did find ∼30% of replicates had increased resistance ( Todd and Selmecki 2020 ). Another evolution experiment that paired a strong selective pressure with a long period of time between transfers (7 days) in caspofungin (a different class of drug), also found that many evolved diploid lines did not increase in resistance by the end of the 59-day experiment ( Avramovska et al 2021 ). In contrast, increased FLC resistance was evident in the earliest C. albicans evolution experiments, conducted in the T101 background in continually increasing levels of FLC for ∼330 generations ( Cowen et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…A second evolution experiment done at the same subinhibitory level of FLC, however, did find ∼30% of replicates had increased resistance ( Todd and Selmecki 2020 ). Another evolution experiment that paired a strong selective pressure with a long period of time between transfers (7 days) in caspofungin (a different class of drug), also found that many evolved diploid lines did not increase in resistance by the end of the 59-day experiment ( Avramovska et al 2021 ). In contrast, increased FLC resistance was evident in the earliest C. albicans evolution experiments, conducted in the T101 background in continually increasing levels of FLC for ∼330 generations ( Cowen et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these results in POS, very few replicates evolved to a subinhibitory level of FLC increased in FLC resistance (Gerstein and Berman 2020), though a second evolution experiment done at the same sub-inhibitory level of FLC found ∼30% of replicates had increased resistance (Todd and Selmecki 2020). An evolution experiment that similarly paired a strong selective pressure with a long period of time (7 days) between transfers to caspofungin, a different drug class, also found that many evolved diploid lines did not increase in resistance by the end of the 59-day experiment (Avramovska et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to see that both α and β concur in defining line (4). This is what originates the conditional nature of the ECM algorithm, i.e.…”
Section: Supplementary Materialsmentioning
confidence: 93%
“…Ploidy variation can be associated with a response or adaptation to environmental factors (13), and it is a phenomenon commonly detected in cancer cells (14) and several pathogenic fungi (i.e. Cryptococcus neoformans , Candida albicans and Candida glabrata ) and monocellular parasites (46; 35; 16; 54; 53; 19; 4).…”
Section: Introductionmentioning
confidence: 99%